2010
DOI: 10.1016/j.ceb.2010.03.002
|View full text |Cite
|
Sign up to set email alerts
|

FRAP and kinetic modeling in the analysis of nuclear protein dynamics: what do we really know?

Abstract: The binding of nuclear proteins to chromatin in live cells has been analyzed by kinetic modeling procedures applied to experimental data from fluorescence recovery after photobleaching (FRAP). The kinetic models have yielded a number of important biological predictions about transcription, but concerns have arisen about the accuracy of these predictions. First, different studies using different kinetic models have arrived at very different predictions for the same or similar proteins. Second, some of these div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
172
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(173 citation statements)
references
References 55 publications
0
172
0
1
Order By: Relevance
“…Molecules of up to 500 kD are not hindered by nuclear structures and have been shown to diffuse unrestrictedly in the nucleus (Seksek et al, 1997;Gö risch et al, 2005). Furthermore, the size dependency of the diffusion coefficient is small; for globular proteins, the diffusion coefficient is proportional to the inverse of the cube root of the molecular mass (D;M 21/3 ) (Reits and Neefjes, 2001;Mueller et al, 2010). This implies that to be able to explain the difference in the observed diffusion coefficient between free GFP (32.7 6 10.3 mm 2 s 21 , 27 kD) and Rx1 (45-116)-GFP (10.0 6 2.7 mm 2 s 21 , 34 kD) ( Figure 7D), the latter should have a mass of ;30 times higher than free GFP.…”
Section: Nuclear Accumulation Of the CC Can Be Attributed To A Small mentioning
confidence: 99%
“…Molecules of up to 500 kD are not hindered by nuclear structures and have been shown to diffuse unrestrictedly in the nucleus (Seksek et al, 1997;Gö risch et al, 2005). Furthermore, the size dependency of the diffusion coefficient is small; for globular proteins, the diffusion coefficient is proportional to the inverse of the cube root of the molecular mass (D;M 21/3 ) (Reits and Neefjes, 2001;Mueller et al, 2010). This implies that to be able to explain the difference in the observed diffusion coefficient between free GFP (32.7 6 10.3 mm 2 s 21 , 27 kD) and Rx1 (45-116)-GFP (10.0 6 2.7 mm 2 s 21 , 34 kD) ( Figure 7D), the latter should have a mass of ;30 times higher than free GFP.…”
Section: Nuclear Accumulation Of the CC Can Be Attributed To A Small mentioning
confidence: 99%
“…These fluorescent proteins can be attached to cellular proteins by gene fusion and allow monitoring the levels and intracellular distributions of the tagged proteins by fluorescence microscopy at high temporal and spatial resolutions. Studies combining GFP-tagging of repair proteins with the induction of localized DSBs [43] and the use of dynamic imaging approaches, such as fluorescence recovery after photobleaching (FRAP, reviewed in [44][45][46][47][48][49][50][51][52]), fluorescence loss in photobleaching (FLIP; reviewed in [46,49,53]) and more recently in vivo fluorescence correlation spectroscopy (FCS; reviewed in [54][55][56][57]), have provided a wealth of knowledge about the spatiotemporal kinetics of repair proteins at DSBs.…”
Section: Insights From Short-term Live-cell Imaging Of the Ddrmentioning
confidence: 99%
“…With the correct mathematical models for the diffusion and "reaction" in the spot, it should be possible to estimate binding and transport parameters for proteins. 34 Using arguments based on models of reaction and diffusion, we developed approaches to identify the rate-limiting step. We showed that, with the correct experimental design, recovery during fluorescence photobleaching for adhesion proteins in living endothelial cells is not limited by diffusion.…”
Section: Mechanical Control Of Intermolecularmentioning
confidence: 99%
“…34 In a cell that expresses this fluorescent, chimeric protein, a spatially defined small area of interest is exposed to a short pulse of high-intensity irradiation at the excitation wavelength of the fluorophore. This exposure photobleaches the fluorophore, causing the area of interest to appear "dark" locally (see Figure 3); the photobleaching does not disrupt the function of the target molecule, so that the protein of interest, while physically present, is rendered optically invisible.…”
Section: Mechanical Control Of Intermolecularmentioning
confidence: 99%